Influence of gender and estrous cycle in the forced swim test in rats - Gouveia Jr., Amauri; Afonseca, Taciana Lucas [UNESP]; Maximino, Caio; Dominguez, Roberto; Morato, Silvio (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), 2008)
The present work aimed at studying the influence of the estrous cycle in the forced swim test, an animal model of depression. For this, 44 male and female Wistar rats were divided into five groups according to the hormonal state in the first day of the study: metaestrus (N = 12), diestrus (N = 8), proestrus (N = 7), estrous (N = 6) and males (N = 11). They were housed in groups of five, with water and food ad libitum under a 12/12 h light/dark cycle. Females were screened daily for the estrous cycle. The animals were subjected to two swimming sessions in a glass cylinder with water up to 15 cm at 28±2º C. The data of the first five minutes of a 15-min first session were compared to those of a 5-min second session 24 h later. The results indicate that the latency to the first immobility was substantially reduced in the second session and was longer for females in diestrus and proestrus in the first session. The results also indicate that females in diestrus and proestrus exhibited less immobility than males in the first session; females in diestrus also exhibited less immobility than females in metaestrus. Females in metaestrus and diestrus, as well as males, did not present the decrease in total immobility times in the second session. The present results are analyzed in terms of differential effects of progesterone and estrogen on a learning component and an affective component.
Keywords: Forced swim test; estrous cycle; sex differences